Aceh’s Crescent and Star Flag: Negotiation of Collective Identity in Post-conflict Aceh VS Indonesia: Muhammad Ansor - Muhammad Ansor (Samudra Publisher, 2023)
The following article analyzes the post-conflict Aceh identity negotiation based on the case study of Aceh’s Crescent and Star Flag also known as the Aceh’s Flag. The paper focuses on tracing the process of collective Aceh identity negotiations as reflected in Aceh’s Crescent and Star Flag discourse, and to the extent of the effectiveness of the establishment of the Aceh flag as a strategy for reformulating the collective identity after the conflict. The following article uses a socio-anthropological approach. The research locations are four regions in Aceh, Banda Aceh, East Aceh, Langsa, and Central Aceh. Semi-structured interviews were conducted against the political elite in Aceh from the pro- and anti-Flag of the Crescent and Star, as well as the central government in Jakarta. Documentation studies were carried out by scrutinizing mass media reports on topics that became research issues. The paper concludes that the diversity of responses of the Aceh community in response to the establishment of the Crescent and Star as the flag of Aceh is a reflection of the social political and cultural diversity that Aceh society is seeking to form a post-conflict collective identity.